Utilización de herramientas web 2.0 en cursos de Química Orgánica a nivel universitario - Romero, Rosaura M. (2015)
One of the challenges facing the world today is to provide a quality education to all its inhabitants, because it is considered that education is the response to development. A possible solution is the use of Web 2.0 tools to support the educational process, however, there is no consensus in if there are benefits from its use. Web 2.0 tools are defined and examples on its integration into organic chemistry teaching in Higher Education are provided.